A Fat Client OS Architecture Supported by Semi-network Resources - Zhang, Yin Sheng (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – This study is to explore a way to retain the strengths and eliminate the weaknesses of the existing architecture of local OS and cloud OS, then create an innovative one, which is referred to as semi-network OS architecture. Method – The elements of semi-network OS architecture includes network resources, local resources, and semi-mobile hardware resources; among them, network resources are the expanded portion of OS, which is used to ensure the scalability of OS; local resources are the base portion of OS, which is used to ensure the stability of local computing, as well as the autonomy of user operations; the semi-mobile hardware resource is OSPU, which is used to ensure the positioning and security of data flow. Results – The fat client OS relies on the network shared resources, local exclusive resources, and semi-mobile hardware resources (OSPU), not relies solely on a single resource, to perform its tasks on a fat client, in this architecture, most of the system files of OS on a fat client is derived from OS server, which is a network shared resources, and the rest of system files of OS is derived from OSPU of a fat client, which is a non-network resource, so the architecture of OS has "semi-network" attribute, wherein the OSPU is a key subordinate component for data processing and security verification, the OS server is a storage place rather than operating a place of system files, and system files that stored on a server can only be downloaded to a fat client to carry out their mission. Conclusion – A complete OS is divided into base portion and expanded portion, and this "portion" division of OS enables a fat client to be dually supported by remote network resources and local non-network resources, therefore, it is expected to make a fat client more flexible, safer and more reliable, and more convenient to be operated.